The Perception of Information and Its Role in Exercising Military Leadership - Kacała, Tomasz (Journal of Corporate Responsibility and Leadership, 2020)
Purpose: The main purpose of the research was to investigate the way the information is perceived and the role it plays in exercising military leadership, especially in the context of differences between the Allied interpretations of the term and the Russian concept of information as an instrument of military strategy. The aim of the paper was to find out, indicate and describe the role and perception of information in different areas of military interest, both within the Alliance and outside of this. Operationalizing the aforementioned aim the following research questions have been set: what are the differences in definitions of information? what are the objectives and principles applied in various kinds of military, information-related activities? what is the role of information in exercising leadership? Design/methodology/approach: Research methodology examined from the perspective of its objectives, in this case, can be classified as descriptive (describing systematically the perception of information, providing required input of expertise and attitudes towards the role of information) and explanatory (clarifying the differences in understanding the concept of information, e.g. in operations and management). If one considers the perspective of ‘mode of enquiry’, the qualitative approach (aiming at exploring diversity rather than quantifying and emphasizing the description of perceptions rather than their measurement) has been applied here. The basic part of research, for the purpose of the paper development, was literature (doctrinal documents) review as well as subject matter (Russian information-related capabilities and activities) summaries collation. Findings: The research shows that the perceptions of information presented by the Alliance and the Russian Federation differ substantially. The roles played by information in exercising military leadership vary as well. Considering Russian perception of information, its main concept is included in the fundamentals of information confrontation as a form of warfare. The Allied interpretation of the term focuses on data, intelligence and knowledge represented in many diverse forms. Research and practical limitations/implications: The research conduct and its scope were limited by two factors: availability of the most updated doctrinal documents (the Alliance) and access to original sources (Russia). The NATO doctrinal documents, to include policies and allied joint publications, are often subject to a long term revision process and thus may not be up to date in many aspects included in their contents. Whereas, the Russian sources are often classified or characterized by limited accessibility. Originality/value: The differences in the information perception have not been compared in such a set yet, especially internally within the Alliance – Information/Knowledge Management and Information Operations. Moreover, the wider context of Russian understanding of the apparatus applied within the Information Environment, though identified, have not been collated with the Allied approach either. Paper type: research paper.